Implementation of the Multi Factor Evaluation Process (MFEP) Method in Making Decisions on Providing Assistance to Underprivileged Students - Netti Susanti (The IJICS (International Journal of Informatics and Computer Science), 2021)
In the activity of receiving Aid for Poor Students, there are several problems, one of which is the distribution of Poor Student Aid funds that are not on target, so that in determining the decision of prospective recipients of Aid for Poor Students, the school must collect various selection files for prospective recipients from student files who come from families. underprivileged to modest. This makes it difficult for the school to make a decision on the recipient of the Poor Student Aid funds. Given the problems faced, this system was created as a means of information to assist schools in selecting prospective recipients of the Poor Student Aid to determine which recipients deserve assistance. This system is in the form of a decision support system (SPK) that can facilitate the school in determining prospective recipients of the Poor Student Assistance, so that the results obtained are effective and efficient